IMPLEMENTASI KURIKULUM MERDEKA DALAM MENINGKATKAN KUALITAS PENDIDIKAN MENEJEMEN KESISWAAN - Jumilah Gago (LPPM Universitas Cipta Mandiri, 2025)
This study is based on the fact that the development of human potential can be processed through educational activities that are usually organized by the government or the private sector. Education can be said to be a life process to develop all the potential that exists in individuals to be able to live and be able to carry out life fully so that they become educated individuals, both cognitively, affectively, and psychomotorically. This study aims to determine the implementation of the independent curriculum in developing the potential of students. The approach used is qualitative with descriptive methods. The results of this study indicate that learning objectives must be able to make students think critically and solve problems, be creative and innovative, be skilled at communicating and collaborating, and have character. Therefore, in planning the implementation of learning activities, they must be able to face challenges and take advantage of educational opportunities in the era of the Industrial Revolution 4.0. And teachers are the key to the success of the independent learning education system, therefore they must be able to adapt to the new education system in order to have skills and competencies. The implementation of the Independent Curriculum has been carried out quite well in the first year, but each School of Mover has the task of how to develop in compiling and implementing this Independent Curriculum so that it can be applied in all its classes, in the current year.